The Impact of Business Intelligence Systems on Human Capital Development at Yemen and Kuwait Bank in the Capital Municipality of Sana'a - Abdulrahman Ahmed Mohammed Manaa; Mohammed Mugahed Saleh Al-Ward (University of Science and Technology, Sana’a, Yemen, 2025)
This study aimed to examine the impact of business intelligence systems on human capital development at Yemen and Kuwait Bank Capital Municipality of Sana'a by assessing the current state of business intelligence adoption and the level of human capital development in the bank. To achieve the study objectives, an analytical descriptive approach was employed, with a questionnaire serving as the primary data collection tool. The study population consisted of all executive employees at Yemen and Kuwait Bank in Sana’a, totaling 307 employees, from which a stratified random sample of 171 individuals was selected. The study utilized descriptive and inferential statistical methods for data analysis, relying on SPSS program. The main findings revealed a statistically significant positive impact of business intelligence systems on human capital development at Yemen and Kuwait Bank. Based on these results, the study provided some practical recommendations.